Lectin histochemistry of microvascular endothelium in chick and quail musculature - Nanka, O; Peumans, W J; Van Damme, E J; Pfüller, U; Valásek, P; Halata, Z; Schumacher, U; Grim, M (Anatomy and embryology, 2001)
The lectin binding pattern of muscular microvessels in chick, quail and chick/quail chimeras was analysed. Paraffin wax sections of muscles from embryonic and adult animals were used. The biotin-labelled lectins were detected by avidin-alkaline phosphatase complex. The following lectins bound to muscular microvessels including arterioles, capillaries and venules of both species: SNA-I (Sambucus nigra agglutinin), MAA (Maackia amurensis agglutinin), AIA (Artocarpus integrifolia agglutinin), VAA-I, VAA-II and VAA-III (Viscum album agglutinin I-III), WGA (wheat germ agglutinin), LEA (Lycopersicon esculentum agglutinin). Endomysium and basement membranes of muscle fibres were also stained to a variable extent and intensity. Only SNA-I stained almost exclusively the endothelium of blood vessels. WFA (Wisteria floribunda agglutinin) bound to the quail endothelium only. MPA (Maclura pomifera agglutinin) marked vessels in adult muscles of chick and quail, but embryonic vessels were stained in quail only. Our results show that lectin histochemistry is a useful tool for visualisation of microvasculature in avian species. In particular, WFA and MPA can be used to determine the origin of endothelia in chick/quail chimeras.
Keywords: kosterní svaly; Chimera; zvířata; imunoenzymatické techniky; Microcirculation; Quail; Muscle, Skeletal; Animals; křepelky a křepelovití; vazebná místa; mikrocirkulace; cévní endotel; lektiny; Binding Sites; Immunoenzyme Techniques; rostlinné lektiny; kuřecí embryo; Lectins; chiméra; Endothelium, Vascular; Plant Lectins; končetiny; Chick Embryo; Extremities